Prevalence Of Feline Lower Urinary Disease (FLUTD) On Cats At Animal Health Centers (Puskeswan) Gorontalo City Period April – Juny 2024 - Erwin Nugroho, Tri Ananda; Apriyanto Paneo (International Journal of Technology and Education Research, 2026)
The aim of this research is to measure the incidence rate (prevalence)of FLUTD cases in cats seeking treatment at the Gorontalo City Animal Health Center (Puskeswan). Feline Lower Urinary Tract Disease (FLUTD) is a disease that often occurs in cats, one of which is coused by the presence of crystals in the urinary bladder. The samples examined were cats that had FLUTD and sought treatment at the Gorontalo City Health Center from July to September 2024. The examination method was to examine the patient’s ambulatory. The patient’s ambulator is the first record when the patient is handled. Cat patients who come have an ananemsa byasking the animal owner several questions, which are then recorded in the ambulatory. After the patient’s analysis is carried out, a physical examination is carried out by measuring body temperature, listening to the respiratory tract using a stethoscope, which aims to find out whether only the digestive system is affected or whether the respiratory system has been attacked. The cat’s urinary bladder is palpated to see if it is hardened and pressure is tried to produce urine. If urine does not come out, it is necessary to install a catheter. The mouth is then opened to determine the condition of the inside of the mouth, whether is has experienced systemic poisoning due to toxins or body waste that cannot be excreted through urine. Cats that have been poisoned will have a purplish color on their oral mucosa. The prevalence of FLUTD in cats receiving treatment at the Gorontalo City Health Center was calculated by dividing patients who showed FLUTD by dividing the number of patients treated during July to September 2024 by one hundred percent. The prevalence of FLUTD in cats seeking treatment from January to March at the Gorontalo City Health Center was 17,70%.